Reduction of tomato losses through implementation of simple postharvest techniques using rosemary (Rosmarinus officinalis) essential oil in Bushi, Democratic Republic of the Congo - Sibomana, I.C. (University of Yaounde, 2020)
Tomato is perishable and its high moisture content makes it susceptible for various postharvest losses. Tomato quality changes continuously after harvesting when fruits start losing quality because of environmental stress and pathogen infection. Thus, the objective of this research was to propose simple postharvest technology using rosemary essential oil (REO) to reduce postharvest decay. This was done by conducting a field survey in order to determine agricultural potential of soil and environmental characteristics of soil used for tomato cultivation in the Bushi region according to the FAO’s land suitability classification; and the compilation of cartographic data was done using ArcGIS 10.3 software. Cultivated fruits in the Bushi region were evaluated based on their morphological characters and data were analysed through XLSTAT package. Laboratory experiments on fresh tomato fruits preservation and tomato processing into juice and paste were done in a central composite design (CCD) using REO to extend the products shelf life in combination with chlorine and Bacillus cereus spores, respectively. Fruit physical and chemical quality characteristics were evaluated, and statistical analyses were done using XLSTAT and STATISTICA packages for non-linear regression analyses. The data obtained were subjected to Analysis of variance (ANOVA) and significant means were separated by mean differences Tukey-HSD test (α ≤ 0.05). Harvested tomato fruits at different maturity stages using REO in a randomized complete block design (RCBD) were evaluated for their chemical quality characteristics and shelf life for implementation in the Bushi region. Data were subjected to ANOVA using R 3.5.1, R Studio 1.1.453 software. Significant means were separated by mean differences Tukey-HSD at α ≤ 0.05. Results indicated that in the Bushi region, soil characteristics and climate data varied from one experimental site to another and that Kabare is theoretically marginally suitable for tomato cultivation compared to Walungu where tomato can be cultivated in moderately and highly suitable areas. During storage, a significant decrease in weight loss (< 10 %) was observed as the REO concentrations increase (500-1000 ppm). The presence of defects was related to the shorter time of immersion in chlorinated water for fruits surface disinfection that immediately impacts on the fruit shelf life. The optimal condition that reduces the percentage defects of fruits was the action of 3 minutes of immersion time in chlorinated water at 200 ppm and high concentration of REO (≥ 500 ppm). Most fruits softened with the increase in fruit colour and prolonged storage time while chlorine and REO concentrations have had a positive influence on the preservation of tomato fresh flavour and on the fruit shelf life extension. High percent reduction (100 %) in Bacillus cereus spores was effective with treatment interactions (cooking time and REO concentrations). In both juice and paste, the percentage reduction of spores depended on the combination of REO with spore concentration and heating time with spore concentration. All treatments in both tomato juice and paste inoculated with 4 log CFU/g have registered variable level of B. cereus inhibition (99.7-100 %), except where there was no heating for deactivation (0.79 %). Total polyphenols, Titratable acidity and Vitamin C content were affected under thermal processing of juice and paste. Independently of the treatments, there was an increase in the total polyphenols content (85.56-220 μg/mg) and a decrease in the vitamin C content of tomato paste (0.47-2.93 mg/mg) compared to tomato juice (40-167.22 μg/ml and 14.4-20.43 mg/ml). For storage efficacy, the contamination with a minimum concentration of Bacillus cereus spores of 104 spores/g was stabilized with treatment at 95°C for 5 minutes in tomato juice and 20 minutes in tomato paste, resulting in a 1 year storage extension. The application of REO alone permitted to extend the shelf life of fresh tomato fruits for preservation in the Bushi region. Soluble solids content in tomato varied significantly (P ≤ 0.05) in fruits of different maturity stages. Vitamin C content was high in fruits of early maturity stages and the shelf life in harvested tomato fruits was evaluated at 14 days of storage, in respect to the percentage of shrivelled fruits. The developed technology for implementation was found to be suitable in the presence of REO by increasing tomato's shelf life.